Innovative teaching methods in physical fitness education: integrating technology and gamification to improve student engagement-a systematic review - Djajati Mariana Lolowang; Fadli Ihsan; Nolfie Piri; Eduard Emor Kumenap; Fredrik Alfrets Makadada (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Background: Physical education plays a vital role in students’ holistic development, yet it often faces low engagement due to monotonous teaching approaches. The integration of technology and gamification has emerged as a promising strategy to enhance motivation and participation in physical fitness education. Objective: This study systematically reviews empirical research on how technology and gamification contribute to student engagement in physical fitness education. Methods: A systematic review method was employed to analyze studies published in the last 15 years, retrieved from academic databases including Google Scholar, PubMed, and Scopus. Inclusion criteria focused on studies involving students and addressing technology and/or gamification in physical fitness education. Results: The review identified multiple studies showing that fitness apps, wearable devices, and virtual reality can significantly enhance motivation and allow real-time performance tracking. Gamification elements such as badges, points, levels, and leaderboards were found to increase participation and foster a competitive yet collaborative learning atmosphere. Several studies reported a 20–30% increase in engagement. However, findings also revealed variation in outcomes depending on context, implementation quality, and access to resources. Some unintended effects, such as performance anxiety from competitive features, were also documented.